Telomerase reverse transcriptase suppression inhibits cell proliferation and promotes cell apoptosis in hepatocellular cancer. Issue 7 (29th April 2018) - Shen, Yanfeng; Xi, Feng; Li, Haibin; Luo, Yin; Chen, Cheng; Wang, Lei
Abstract: We aimed to investigate the role of telomerase reverse transcriptase ( TERT) in hepatocellular cancer (HCC) cells. R software was used for differential expressed gene analysis. Western blot and quantitative real time polymerase chain reaction (qRT‐PCR), respectively, were used to detect protein expression and mRNA level of TERT in tumor cell lines. Real‐time quantitative telomeric repeat amplification protocol assay, MTT assay, colony formation assay, and flow cytometry (FCM) assay were used to analyze the telomerase activity, viability, proliferation, cell cycle progression and apoptosis of HCC cells. The proliferation ratio of HCC cells transfected with TERT ‐siRNA was significantly decreased compared with control group. Plate clone results suggested that the number of colonies also decreased in TERT ‐siRNA group. FCM results showed that more cells were arrested in G0/G1 phase and apoptosis rate increased in TERT ‐siRNA group compared with control group. TERT suppression inhibited cell proliferation but promoted cell cycle arrest and cell apoptosis. © 2018 IUBMB Life, 70(7):642–648, 2018